MOTIVATION AND RELIGIOUS UNDERSTANDING OF STUDENTS IN HIJAB AT MUHAMMADIYAH UNIVERSITY, NORTH SUMATRA - Nur Rahmah Amini; Mahmud Yunus Daulay (Proceeding International Seminar of Islamic Studies, 2022)
The long-term objectives of this research are; Provide input to policy makers at Muhammadiyah University in order to direct the academic community (especially female students) to wear clothes and hijabs that are in accordance with the actual Shari'a. The specific target to be achieved from this research is to provide input and encourage female students to improve their motivation in wearing the hijab which is part of Islamic teachings, namely covering their genitals, and at the same time encouraging female students to increase their knowledge about religion. The method used in this study is a qualitative method, using a phenomenological approach and type of research. Data collection used in the study were interviews and observations. Interviews were conducted to explore the motivation of female students to wear the hijab and to explore their religious understanding. While the observations were carried out in order to see firsthand how the models and patterns of wearing the hijab were carried out. The activity plan is carried out through stages consisting of: data collection as well as data reduction, data presentation and conclusion drawing and data verification. The results of the study explain that students at the Muhammadiyah University of North Sumatra have understood the obligation to wear the hijab with the aim of maintaining aurat and protecting themselves from committing sins.Keywords: Motivating, Understanding, and veiled student